2020
DOI: 10.1002/pls2.10016
|View full text |Cite
|
Sign up to set email alerts
|

Solid state polymer ionogel electrolyte for use in Li‐ion batteries

Abstract: This work presents a preparation method for solid state ionogel electrolyte membranes intended for lithium-ion batteries (LIBs). These membranes are obtained by filling the pores of syndiotactic polystyrene (sPS) gels with an ionic liquid (IL) that is later polymerized. The aim is to improve the thermal stability and mechanical properties in conjunction with mitigation of ionic liquid loss from ionogel electrolyte membranes at high application temperatures (>50 C). Such ionogel membranes circumvent the dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…The BMI‐Br would interact with LiTFSI salt based on the anion exchange in fabricating the electrolyte, forming the BMI‐TFSI salt within the PEO matrix. [ 61 ] Since the TFSI − is scavenged by BMI‐Br with creating BMI‐TFSI salt, the formation of [Li(TFSI) 2 ] −1 clusters would be reduced. [ 56 ] As a result, the reduced clustering can enhance the ion conductivity of Li + in the BMI‐Br‐CPE sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMI‐Br would interact with LiTFSI salt based on the anion exchange in fabricating the electrolyte, forming the BMI‐TFSI salt within the PEO matrix. [ 61 ] Since the TFSI − is scavenged by BMI‐Br with creating BMI‐TFSI salt, the formation of [Li(TFSI) 2 ] −1 clusters would be reduced. [ 56 ] As a result, the reduced clustering can enhance the ion conductivity of Li + in the BMI‐Br‐CPE sample.…”
Section: Resultsmentioning
confidence: 99%
“…Previous similar work also showed that after anion exchange between 1‐ethyl‐3‐vinylimidazolium bromide and LiTFSI, forming VI‐TFSI and Li‐Br. [ 61 ] Here, BMI‐TFSI acts as an ionic liquid, while Li‐Br serves as a salt. [ 61 ] Schematic of the ionic conduction mechanisms in SPE and BMI‐Br‐CPEs is shown in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…The tensile strength for all series of the 10% LiClO 4 ‐complexed MC/CMC (50/50)‐based BBE doped with [EMIm]Ac are higher compared with previous polymer electrolytes which were reported. [ 46,58 ]…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids (ILs) are normally defined as compounds composed entirely of ions with melting point below 100 C. [21,22] An IL consists of an organic cation and an organic or inorganic anion, and is well known for its low vapor pressure, non-flammability, good thermal and chemical stability [23][24][25][26] and flexible structure design. [27] So far, ILs have been widely applied in the fields of analytical chemistry, [28,29] electrochemistry, [30][31][32] polymerization [33,34] and gas absorption/separation. [35][36][37][38] In the last decade, the potential applications as an effective and eco-friendly surface modification agent for fillers in rubber materials have also aroused great interest.…”
Section: Introductionmentioning
confidence: 99%